2023
DOI: 10.1371/journal.pone.0281593
|View full text |Cite
|
Sign up to set email alerts
|

The possible onset of fibromyalgia following acute COVID-19 infection

Abstract: Introduction The exact pathogenesis of fibromyalgia (FM) syndrome is unclear. However, various infectious have been implicated with the development of FM after their acute phase. We aimed to investigate the incidence of FM syndrome among convalesced individuals following hospitalization for Acute Coronavirus Disease-2019 (COVID-19). Methods We performed a cross-sectional study on patients who were discharged after COVID-19 hospitalization from the Sheba Medical Center, Israel, between July 2020 to November 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
3
4
0
1
Order By: Relevance
“…Moreover, our results have shown that neither hospitalization nor the need for supplemental oxygen were significantly correlated with the development of fibromyalgia. This was concordant with the results of Savin et al [ 20 ]. However, Ursini et al stated that there was a significantly higher prevalence of fibromyalgia among those who required oxygen supplementation during their COVID-19 infection [ 14 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, our results have shown that neither hospitalization nor the need for supplemental oxygen were significantly correlated with the development of fibromyalgia. This was concordant with the results of Savin et al [ 20 ]. However, Ursini et al stated that there was a significantly higher prevalence of fibromyalgia among those who required oxygen supplementation during their COVID-19 infection [ 14 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is in accordance with the results of Savin et al, as they reported that 15% of their included sample developed fibromyalgia after being discharged following recovery from COVID-19 infection [20]. The 5% difference between the two studies could be explained by the difference in data collection methods, as we utilized a web-based questionnaire while Savin et al collected patients' responses via an interview [20]. In our study, female gender was found to be an independent risk factor for developing fibromyalgia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Three-quarters of these patients were women, and their mean age was 45 years. Of 200 hospitalized patients 5 months after SARS-CoV-2 infection, 15% met FM diagnostic criteria, and 87% had at least one FM-related symptom, including fatigue in 57%, unrefreshing sleep in 56%, cognitive disturbances in 54%, and muscle or joint pain in 42% (12).…”
Section: Similar Symptoms Of Fm and Me/cfs In Long Covid Syndromementioning
confidence: 99%
“…A experiência da dor em pacientes portadores de FM pode variar conforme o estado emocional do indivíduo, das condições imunológicas e comorbidades associadas, especialmente aquelas relacionadas a distúrbios metabólicos (hipertensão e diabetes)(RIVERA, 2021).A pandemia da COVID-19, causada pelo vírus da Síndrome Respiratória Aguda Grave 2 (SARS-COV-2) no início de 2020, foi marcada por um longo período de anseio, aflições e estresse gerado, principalmente, pelo medo da doença até então desconhecida e pelo isolamento social. Entre as complicações mais comuns a longo prazo, trata-se do desenvolvimento de sintomas como o comprometimento cognitivo, alterações do humor e do sono, cefaleia, distúrbios sensoriais (olfato e paladar afetados), ansiedade e depressão(SAVIN, 2023). A evolução do quadro clínico para além da fase aguda da doença consiste nos sintomas pós-COVID19, normalmente, as manifestações secundárias costumam estar associadas à maior gravidade da infecção.…”
unclassified